The 52-hour work week in South Korea - KIM, Ki Sung (KDI School, 2023)
Despite exhibiting a continuous and downward trend in working hours, South Korea nonetheless maintains one of the highest working hours in the OECD. To combat this, previous administrations phased in the 40-hour work week from 2004 to 2011, with mixed results. More recently, an overtime cap reform began phasing in since 2018, essentially confining the maximum weekly working hours to 52 for workers falling within its scope. This paper addresses the question of whether or not working hours were actually reduced by this policy. In other words, did the reform have the desired effect? If this is not the case, then it is hard to imagine that the perceived benefits of reduced working hours (work-life balance, physical and mental health, etc.) have been gained in tandem. Preliminary research as regards this policy generally conclude that working hours were indeed reduced, but I find that may not be the case. Panel data from the Korea Labor Institute was utilized, and various statistical methods were deployed (i.e. fixed effects, difference-in-differences, propensity matching, regression discontinuity). Taken as a whole, the results show that working hours were not significantly reduced by this policy. This implies that similar mistakes were made as in the implementation of the 40-hour work week and/or new mistakes were made in the context of a perpetually changing labor environment. Limitations and directions for future research are discussed, but more importantly, the results of this paper highlight the importance of proper implementation of a well-intentioned policy, as well as having a proper backdrop for such a policy to be carried out effectively. Furthermore, people who fall within the scope of such a policy must be in a position where they are able to benefit from it. In other words, if there are no viable alternatives to overwork, people will continue to do so.
Thesis(Master) -- KDI School: Master of Public Policy, 2023
Keywords: Hours of labor--Korea (South); Labor time--Korea (South)